PENGARUH SENAM TERA TERHADAP PERUBAHAN TINGKAT STRES WANITA BALI DENGAN TRIPLE ROLES - Luh Gede, Prabayati (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Stress is a body respon to a psikososial stressor. Most stress experienced by women, expecially a balinesse woman with triple roles in their life. One of therapies that can affect stress is Tera Exercise. This research is a quasy-experimental study (pre-test and post-test with control group design). This research was conducted on Juli 1. Samples consist of 30 respondent were selected by purposive sampling, and divided into two groups, intervention and control. The intervention group was given 12 times Tera Exercise for 1 month. Stress measurement was carried out by using Depression Anxiety Stress Scales (DASS) questionnaire of which the validity and reliability have been tested. The tests are used to determine the relationship of independent variables and the dependent variable in this study are independent sample t-test. Based on independent sample t-test, this difference was statistically significant, with Sig. (2 tailed) of 0.000, which means there is the effect of Tera Excersice for Excange of Stress level in Women with Triple Roles at Tegehkuri, Tonja, Denpasar. Based on the result, officials of Tonja need to apply Tera exercise regularly to improve the quality of life by reducing level of stres of women with Triple roles. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Balinese Triple roles women, Tera Exercise, Stress